Sexual stature dimorphism as an indicator of living standards?. (1st November 2016) - Sohn, Kitae
Abstract: Background : A group of researchers has argued that sexual stature dimorphism (SSD) can serve as an indicator of living standards. This argument is based on evidence that boys' physical growth is more sensitive to environmental conditions than girls' physical growth. Because Korea's economic growth in the second half of the 20th century was unprecedentedly rapid, according to their logic, it is likely to see an increasing trend in SSD. Aim : We aimed to determine whether SSD can serve as an accurate indicator of living standards for a population that would exhibit a pronounced trend in SSD, providing that the logic for use of SSD is correct. Subjects and methods : We employed nationally representative Korean men born in 1941–1990 ( n = 17 268) and women born in 1941–1991 ( n = 22 543) and estimated mean heights by sex and birth years. We then calculated SSD values and charted the trend. Results : Although male height increased faster than female height, the SSD trend was flat for the pooled observations and for sub-groups by socioeconomic status. Conclusion : These results cast doubt on the argument for using SSD as an indicator of living standards.